Coaching in an Educational Setting Utilizing “Techniques of Change”: Enhancing Engagement with Learning in a Post-16 Educational Setting - Voldis Kudliskis (Educational Process: International Journal)
The purpose of this study was to explore whether or not Techniques of Change associated with Neuro-linguistic Programming (NLP) could enhance engagement with learning for boys in the post-16 education setting. This was an action research case study that utilized a mixed methods approach. Participants were coached by a qualified NLP practitioner and used NLP workbooks to aid and enhance understanding of “Techniques of Change” associated with NLP. Participants also engaged with a pretest and posttest questionnaire and participated in semi-structured interviews. The study predominantly sits within the interpretivist paradigm. It is a single-site, multi-voice study. “Positions of Consensus” are presented in relation to Techniques of Change enhancing boys’ engagement with learning. The outcome of this research provides some speculative evidence that Techniques of Change can enhance engagement with learning for Year 13 males. This study provides educationalists, managers, teachers and parents with an opportunity to consider how a specific form of coaching may encourage enhanced engagement and enriched learning outcomes for boys in post-16 education. This, in turn, may lead to greater positivity in their specific educational context and broader social interactions.